Physicochemical properties of three Yunnan cigar tobacco leaves and identification of aroma compounds in tobacco smoke - Chen, Dan; Chen, Haitao; Sun, Haowei; Man, Yifei; Long, Jie; Liu, Mengying; Cai, Jieyun; Li, Dan; Xu, Shibin; Liu, Kai; Wang, Shuqi (Frontiers in Chemistry, 2025)
IntroductionThis study focused on three kinds of cigar tobacco leaves (Yunxue 6, Yunxue 36, Yunxue 2) produced in Yunnan region, and through the systematic analysis of their physicochemical properties and aroma components of the smoke, the transformation pattern of aroma compounds and their origins during combustion were deeply investigated.MethodsIn the experiments, gas chromatography-mass spectrometry (GC-MS) and gas chromatography-olfactometry-mass spectrometry (GC-O-MS) techniques were used to comprehensively qualitatively and quantitatively analyze the volatile constituents in the tobacco and its smoke, and combined with the conventional chemical composition detection, to reveal the physicochemical properties of Yunnan cigar tobacco and its influence mechanism on the smoke flavor.ResultsYunnan cigar tobacco exhibits distinct chemical characteristics with low sugar (0.12%–0.16%), high nitrogen (2.84%–4.56%) and alkaloid (2.32%–5.56%) contents, along with imbalanced nitrogen-alkali and potassium-chlorine ratios, affecting its combustion and sensory properties. Smoke analysis identified 144 volatile compounds, predominantly heterocyclic, aromatic and olefinic substances, with elevated pyrazines and pyridines contributing roasted, nutty and smoky notes. GC-O-MS analysis revealed 51 key aroma-active components, demonstrating greater complexity in core tobacco (YXYY) than wrapper tobacco (DHYY, PEYY).DiscussionCombustion transforms precursors (carotenoids, cedranes, phenylalanine) into characteristic aromas through pyrolysis and Maillard reactions, enhancing flavor complexity. This study first elucidates the chemical basis of Yunnan cigar’s characteristic aroma, providing theoretical support for quality improvement, process optimization and product differentiation in domestic cigar production. It fills research gaps in Chinese cigar aerochemistry and establishes a foundation for precision cultivation (e.g., chlorine regulation) and targeted fermentation processes to enhance cigar quality.